Kajian Literatur: Matematika pada materi Penyajian Data Siswa Sekolah Dasar dan Solusinya - Aprilia Aisyah Astuti; Adzani, Nasywa Kamila; Futri Aysah; Fatkhul Arifin (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2024)
An study of typical mathematical difficulties primary school pupils encounter while trying to grasp data presentation material is presented in this article. Through a qualitative method, this research seeks to identify the primary challenges faced by students and offer workable answers. The research approach is a study of the literature, looking at many publications from 2014 to 2024 with an emphasis on conclusion identification analysis. According to the findings, students' primary challenges include comprehending foundational mathematical ideas, lacking motivation and enthusiasm in their studies, and a dearth of useful resources and instructional strategies. Diagnostic assessments, project-based learning (PjBL), interactive teaching materials, the use of visual aids, regular evaluation and feedback, and the application of educational technology are some of the suggested remedies. These findings' practical ramifications emphasize the need for a better method of teaching mathematics to primary school pupils that emphasizes conceptual comprehension and contextual application.